Antibacterial Ferroelectric Hybrid Membranes Fabricated via Electrospinning for Wound Healing; Membranes; Vol. 11, iss. 12 - Lukiev I. V. Ivan Vasiljevich; Antipina L. S. Ludmila Sergeevna; Goreninsky (Goreninskii) S. I. Semen Igorevich; Tverdokhlebova T. S. Tamara Sergeevna; Vasilchenko D. V. Dmitry Vladimirovich; Nemoykina A. L. Anna Leonidovna; Goncharova D. A. Darjya Aleksandrovna; Svetlichniy V. A. Valery Anatoljevich; Dambaev G. T. Georgy Tsyrenovich; Buznik V. M. Vyacheslav Mikhaylovich; Bolbasov E. N. Evgeny Nikolaevich (2021, 2021)
Title screen